Long-Term Outcomes of Randomized Controlled Trials Comparing Percutaneous Left Atrial Appendage Closure to Oral Anticoagulation for Nonvalvular Atrial Fibrillation: A Meta-Analysis - Madhavan, Mahesh V; Howard, James P; Brener, Michael I; Der Nigoghossian, Caroline; Chen, Shmuel; Makkar, Raj; Osmancik, Pavel; Reddy, Vivek Y; Holmes, David R; Stone, Gregg W; Leon, Martin B; Ahmad, Yousif (Structural heart, 2023)
BACKGROUND: Oral anticoagulation (OAC) has been considered the standard of care for stroke prophylaxis for patients with nonvalvular atrial fibrillation; however, many individuals are unable or unwilling to take long-term OAC. The safety and efficacy of percutaneous left atrial appendage closure (LAAC) have been controversial, and new trial data have recently emerged. We therefore sought to perform an updated meta-analysis of randomized clinical trials (RCTs) comparing OAC to percutaneous LAAC, focusing on individual clinical endpoints. METHODS: We performed a systematic search of the MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials from January 2000 through December 2021 for all RCTs comparing percutaneous LAAC to OAC in patients with nonvalvular atrial fibrillation. Fixed and random effects meta-analyses of hazard ratios (HRs) were performed using the longest follow-up duration available by intention-to-treat. The prespecified primary endpoint was all-cause mortality. RESULTS: Three RCTs enrolling 1516 patients were identified. The weighted mean follow-up was 54.7 months. LAAC was associated with a reduced risk of all-cause mortality (HR 0.76; 95% confidence interval [CI], 0.59-0.96; p = 0.023), hemorrhagic stroke (HR 0.24; 95% CI, 0.09-0.61; p = 0.003), and major nonprocedural bleeding (HR 0.52; 95% CI, 0.37-0.74; p < 0.001). There was no significant difference between LAAC and OAC for any other endpoints. CONCLUSIONS: The available evidence from RCTs suggests LAAC therapy is associated with reduced long-term risk of death compared with OAC. This may be driven by reductions in hemorrhagic stroke and major nonprocedural bleeding. There were no significant differences in the risk of all stroke. Further large-scale clinical trials are needed to validate these findings.
Keywords: Stroke; Meta-analysis; Atrial fibrillation; Left atrial appendage closure